2019
DOI: 10.1111/dom.13868
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of naringenin: A randomized, controlled, single‐ascending‐dose clinical trial

Abstract: Aims To evaluate the safety and pharmacokinetics of naringenin in healthy adults consuming whole‐orange (Citrus sinensis) extract. Methods and methods In a single‐ascending‐dose randomized crossover trial, 18 adults ingested doses of 150 mg (NAR150), 300 mg (NAR300), 600 mg (NAR600) and 900 mg (NAR900) naringenin or placebo. Each dose or placebo was followed by a wash‐out period of at least 1 week. Blood safety markers were evaluated pre‐dose and 24 hours post‐dose. Adverse events (AEs) were recorded. Serum na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 43 publications
1
69
0
Order By: Relevance
“…PMFs are generally quite safe, which is a major advantage. It has been shown that chronic administration of the extract of Citrus reticulata Blanco , Citrus reticulata or Citrus sinensis , which contain high concentrations of PMFs, have no harmful effects on animals [ 168 , 169 ], and humans [ 170 , 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…PMFs are generally quite safe, which is a major advantage. It has been shown that chronic administration of the extract of Citrus reticulata Blanco , Citrus reticulata or Citrus sinensis , which contain high concentrations of PMFs, have no harmful effects on animals [ 168 , 169 ], and humans [ 170 , 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a single ascending-dose randomized controlled trial of 18 adults by Rebello et al , no adverse effects or changes in blood safety biomarkers were observed after oral consumption of 150–900 mg naringenin, the flavonone form of naringin, relative to placebo. 117 Measured serum biomarkers included alanine aminotransferase, creatinine phosphokinase, and potassium, as well as total white blood cell and eosinophil counts as markers of immune system activation. At these doses, naringin metabolites freely circulate and are effectively cleared from the body within 24 h of ingestion.…”
Section: In Vivo Modeling Of the Restorative Effects Of Naringin In Pmentioning
confidence: 99%
“…The quantification of naringenin in the extract, and the safety and pharmacokinetics of the extract in humans are previously described. 15 The extract contained 28% naringenin. Therefore, each capsule prepared by the PBRC pharmacist contained 536 mg of the extract.…”
Section: Whole Orange Extractmentioning
confidence: 99%
“…14 We have previously shown that an aqueous and ethanolic extract of whole sweet oranges (Citrus sinensis) containing naringenin, the free aglycone form, can be readily absorbed from the small intestine and is present in human serum at concentrations sufficient to elicit a physiologic response. 15 We hypothesized that naringenin supplementation for 8 weeks would increase resting metabolic rate (RMR) and insulin sensitivity in humans. We also explored the mechanisms by which naringenin mediates thermogenesis and glucose metabolism in differentiated human adiposederived stem cells (hADSCs).…”
Section: Introductionmentioning
confidence: 99%